Global streaming platforms and national pay-television markets: a case study of Netflix and multi-channel providers in Israel. Issue 1 (2nd January 2020) - Wayne, Michael L.
ABSTRACT: This research offers a "helicopter view" of the Israeli pay-television market eighteen months after Netflix's global expansion to complicate the narrative of intractable conflict between subscription video on-demand (SVOD) platforms like Netflix and national television industries. Using data from qualitative interviews with ten industry executives, this article argues that relationships between global SVODs and local television providers are more varied than is widely believed. Israeli multi-channel executives consider Netflix to be an indirect competitor, view Netflix the content distributor as distinct from Netflix the content buyer, and expect Netflix to have little impact on the national market. Ultimately, these industry responses reaffirm the fundamental local-ness of television even as digital technology reshapes the relations between national and global industries.